Unlocking the relationship between capital flows and economic growth in a small open economy of Kenya: An empirical investigation - Omolola Oluwatoyin Adeola; Meshach Jesse Aziakpono (Cogent Economics & Finance, 2022)
This study examines the relative effects of the different types of international financial flows on economic performance in Kenya both in the long- and short-runs using the autoregressive distributed lag model (ARDL) bounds approach and data for the period 1970 to 2017. This is against the backdrop of the government of Kenya which has targeted attracting foreign capital inflows as one of the key measures to achieving the economic pillar of the Kenya Vision 2030. The aim is to achieve an economic growth rate of 10 per cent annually and sustaining the same until 2030. After a very rigorous and careful model selection exercise, the results robustly reveal a very strong long-run causality running solely from portfolio equity to economic growth with a positive and significant effect on economic growth. In the short-run, the effect of portfolio equity on economic growth is also very positively strong. In contrast, all the other capital flows have very weak long-run relationship with economic growth with causality running only from economic growth to the capital flows.
Keywords: C32; F21; F24; 330; foreign capital flows; economic growth; Kenya; ARDL